A new proof of Frank-Weissenborn inequality - Gol’‎dberg, Anatoly (Журнал математичної фізики, аналізу, геометрії, 2005)
A new proof of the Frank-Weissenborn inequality is given. This proof uses the theory of algebroid functions.Mathematics Subject Classification: 30D35